Peran Komunikasi Berbasis Empati dalam Meningkatkan Interaksi Guru dalam Mengajar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The interaction between teachers and students plays a crucial role in creating an effective learning environment. Empathy-based communication is an approach that can enhance the quality of interaction by understanding students' emotional and academic needs. This study aims to analyze the role of empathetic communication in supporting the teaching process. A qualitative research approach was employed, with a case study conducted at SDN 060842 Sekip Medan. Data were collected through observations and interviews with homeroom teachers. The findings indicate that empathy-based communication can increase student participation, create a positive learning environment, and help teachers identify learning obstacles. However, the implementation of empathetic communication still faces challenges, such as teachers' workload and time constraints. Therefore, training and policies that support its implementation in schools are necessary. This study emphasizes that empathetic communication is not just a teaching strategy but also a means of building stronger and more harmonious relationships between teachers and students.